Are the intensities and durations of small-scale pottery firings sufficient to completely dehydroxylate clays? Testing a key assumption underlying ceramic rehydroxylation dating. (March 2017) - Paige, Jonathan; Michelaki, Kostalena; Campisano, Christopher; Barton, Michael; Heimsath, Arjun
Abstract: Rehydroxylation (RHX) dating was recently suggested as a simple, cheap, and accurate method for dating ceramics. It depends on the constant rate of rehydroxylation (the slow reintroduction of OH) of clays after they are fired and dehydroxylated (purged of OH) during the production of pots, bricks, or other ceramics. The original firing of the ceramic artifact should set the dating clock to zero by driving all hydroxyls out of the clay chemical structure. To examine whether this assumption holds, especially for pot firings of short duration and low intensity, as those in small-scale traditional settings, we performed thermogravimetric analysis of clay samples of known mineralogy at temperatures and for durations reported from traditional sub-Saharan, American, and South Asian pottery firings. Results demonstrate that in the majority of samples, complete dehydroxylation (DHX) did not occur within, or even beyond, the conditions common in traditional firings. Consequently, between 0.01 and 1.5% of a sample's mass in residual OH may remain after firings analogous to those observed in the ethnographic record. Lack of complete DHX at the scales we have observed can result in the over-estimation of ceramic ages by decades to tens of thousands of years, depending largely on the age of the sample, and the amount of residual OH present. Thus, in many cases, a key assumption underlying current RHX dating methods is unlikely to have been met, introducing considerable error in dates. Highlights: Ceramic rehydroxylation dating (RHX) has been proposed as a new means of dating prehistoric ceramics. RHX methods assume when a pot was fired in prehistory it was completely dehydroxylated. Firing intensities and durations analogous to prehistoric firings are insufficient to dehydroxylate clays. Even conservative estimates of residual hydroxyls would cause overestimation of RHX dates by decades to millenia.